2022
DOI: 10.1002/jcla.24304
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0007142 contributes to cisplatin resistance in esophageal squamous cell carcinoma via miR‐494‐3p/LASP1 axis

Abstract: Background Chemoresistance is one of the major obstacles for tumor treatment. Circular RNAs (circRNAs) have been confirmed to play vital roles in chemoresistance of cancer, including esophageal squamous cell carcinoma (ESCC). We investigated the roles and mechanisms of circ_0007142 in cisplatin (DDP) resistance of ESCC. Methods Quantitative real‐time polymerase chain reaction (qRT‐PCR) was conducted to determine the levels of circ_0007142, DOCK1 mRNA, microRNA‐494‐3p (miR‐494‐3p) and LIM And SH3 Protein 1 (LAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Further evidence to support the role of miR-494 in overcoming chemoresistance came from Peng and colleagues, who investigated acquired drug resistance of gastric cancer cells and demonstrated an impact of miR-494 in the recovery of chemoresistance against doxorubicin [ 79 ]. Moreover, Chang and colleagues showed that the depletion of miR-494 by a circular RNA contributes to cisplatin resistance [ 80 ]. Another possible aspect for future therapeutic considerations regarding miR-494 could be its use within combinatorial therapy strategies that can target more than one pathway of cancer cells; here, various kinase inhibitors, such as imatinib, sorafinib, trastuzumab, or osimertinib, already considered for dual therapy in CRC, would be interesting partners [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence to support the role of miR-494 in overcoming chemoresistance came from Peng and colleagues, who investigated acquired drug resistance of gastric cancer cells and demonstrated an impact of miR-494 in the recovery of chemoresistance against doxorubicin [ 79 ]. Moreover, Chang and colleagues showed that the depletion of miR-494 by a circular RNA contributes to cisplatin resistance [ 80 ]. Another possible aspect for future therapeutic considerations regarding miR-494 could be its use within combinatorial therapy strategies that can target more than one pathway of cancer cells; here, various kinase inhibitors, such as imatinib, sorafinib, trastuzumab, or osimertinib, already considered for dual therapy in CRC, would be interesting partners [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…LASP1 is an actin-binding protein, and overexpression of LASP1 is associated with poor prognosis in patients with gastric cancer ( Keckesova et al, 2017 ). After the downregulation of LASP1 , the resistance of osteosarcoma cells to cisplatin was reduced, the IC50 decreased, and the knockdown of LASP1 could result in the inhibition of the proliferation of osteosarcoma cells ( Chang et al, 2022 ). LACTB is a mitochondrial protein that is highly expressed in skeletal muscle, heart, and liver ( Keckesova et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zou FW reported that circ_001275 was upregulated in cisplatin-resistant esophageal cancer tissues and cell lines and that circRNA_001275 promoted the proliferation of cisplatin-resistant cells ( 38 ). Chang et al found that circ_0007142 was increased in cisplatin-resistant ESCC and that silencing of circ_0007142 enhanced cisplatin sensitivity in ESCC ( 39 ).…”
Section: Discussionmentioning
confidence: 99%